LANGUAGE IMAGERIES/SYMBOLS UTTERED BY KING LEAR HIMSELF IN KING LEAR TRAGEDY - Mangantar Sitohang (STIBA IEC JAKARTA, 2017)
This research attempts to analyze Shakespeare language symbols/imagery in King Lear (Tragedy Drama). It is generally agreed that there are always many factors why a playwright is still remembered from a century to next centuries, and among many factors that could make someone always well-known/remembered is his/her language factor beside the theme or the messages s/he wanted to convey, of course. King Lear had succeeded to choose the right rhetoric devices or signs in his period and wonder many people are still amazed / inspired up to now due to his unique and rich language. His symbols / imagery, combined with verse and prose in King Lear can express penetratingly the essence of a thing, emotion or situation in term of another, thus convey the sharpness of one’s own vision and sensitivity one’s reader or spectator, again the imagery / symbol here, are connected aspects or angles of people’s lives, and all are interwoven beautifully, and again it’s the language quality of King Lear that makes the researcher is tempted to observe it.